Are Old News Release Format Rules Valid In an Electronics Era? - Terence L. Day (Journal of Applied Communications, 1981)
Print on only one side of the page. Double space. Use only white paper. All of my career I have been told that the above three rules for news release format are cardinal. Violate anyone of them and newspaper editors will brand us as amateurs, hacks, or worse.